On Some Effects of Communication Barriers on the Quality of Candidate Performance and Examiner Judgements - Bekaryan, Lilit; Gyulazyan, Irena (Armenian Folia Anglistika, 2012)
The article centers on the communication barriers which can hinder the process of the interview during international examination tests and affect the quality of the candidate performance and examiner judgments. The investigation reveals that communication barriers are caused by a number of factors including the interference of the native tongue, linguocultural peculiarities of the candidates, misunderstandings in the process of the exam, low level of language competence.